Defense and sea security based on law No. 32 of 2014 concerning marine. (February 2019) - Abdullah, L O D; Nurcahyo, E; Pratiwi, E T; Abdullah, R; Tambaru, R; Irwansyah,; Ilyas, A
Abstract: What is the core of this research is about Defense and Marine Security based on Law No. 32 Year 2014 About Marine. Explanation of maritime law has been regulated by the defense and security at sea as contained in CHAPTER IX concerning Defense, Security, Law Enforcement and Safety at Sea as stated in articles 58, 59, 60, 61, 62, 63, 64, 65, 66.67 and 68. Even though it is clear in Law No. 32 Year 2014 concerning the Sea is mentioned clearly about the importance of defense and security for the prosperity or unity of the Republic of Indonesia and the concept of state security is the obligation of all citizens, as stated in the 1945 Constitution, Article 27 paragraph 3, which states that "every citizen the state is entitled and obliged to participate in the defense of the state ". Article 30 paragraph 1, reads "every citizen shall have the right and obligation to participate in the defense and security of the state". Article 30 paragraph 1, reads "every citizen shall have the right and obligation to participate in the defense and security of the state". Article 30 paragraph 2, reads "The business of national defense and security is carried out through the system of defense and security of the universal people by the Indonesian National Army and the National Police of the Republic of Indonesia, as the main force, and the people, as a supporting force". and Article 30 paragraph 3, reads "The Indonesian National Army consists of the Army, Navy and Air Force, as the state's instrument in charge of maintaining, protecting and maintaining the integrity and sovereignty of the state".